EPISTEMOLOGI DAN RUMPUN KEILMUAN KOMUNIKASI PENYIARAN ISLAM - Mohammad Zamroni (Jurnal Ilmu Dakwah, 2014)
As a field of scientific discipline, the existence of Islamic communication and broadcasting still seems to be an unanswerable question. The issue is often addressed on how the epistemology and the clumps of communication and broadcasting science is. To meet this problem, in-depth studies need to be done by tracing the philosophy of science as a basic science including ontology, epistemology, and axiology. This study is needed to dismiss such dichotomy between secular sciences and the religious sciences (Islam). An integrative-interconnected science paradigm becomes a reference of the approach to integrate between science and Islam. Thus, the epistemology of communication science is a scientific discipline that studies broadcasting and journalism like others. While the Islamic Broadcasting Studies is a field of Da’wa study that becomes a core value of the Islamic perspective.*** Sebagai bidang disiplin ilmu, adanya komunikasi Islam dan penyiaran nampaknya masih menjadi pertanyaan yang tidak terjawab. Masalah ini sering ditujukan pada bagaimana epistemologi dan rumpun komunikasi dan ilmu penyiaran. Untuk memenuhi masalah ini, studi perlu dilakukan secara mendalam dengan menelusuri filsafat ilmu sebagai ilmu dasar termasuk ontologi, epistemologi, dan aksiologi. Penelitian ini diperlukan untuk mengabaikan dikotomi seperti antara ilmu-ilmu sekuler dan ilmu-ilmu agama (Islam). Paradigma ilmu integratif-saling berhubungan menjadi acuan dari pendekatan untuk mengintegrasikan antara ilmu pengetahuan dan Islam. Dengan demikian, epistemologi ilmu komunikasi adalah suatu disiplin ilmu yang mempelajari penyiaran dan jurnalisme seperti orang lain. Sementara Studi Broadcasting Islam adalah bidang studi Dakwah yang menjadi nilai inti dari perspektif Islam.